2015
DOI: 10.1007/s10157-015-1192-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased storage and secretion of phosphatidylcholines by senescent human peritoneal mesothelial cells

Abstract: Senescent HPMC store and secrete substantially more PC than young cells. Our findings indicate a novel protective mechanism, which should counteract peritoneal damage induced by chronic exposure to PD fluids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…In another study, senescent human peritoneal mesothelial cells were found to store and secrete substantially more phosphatidylcholines than young cells. 56 Our results are also in agreement with another large-scale targeted metabolic profiling study 5 in which there was a significant increase in specific phosphatidylcholines and sphingomyelins. It is suggested that the elevated serum levels of phospholipid in elderly are also involved in protection against oxidative stress; 5 however, further investigation is needed to understand the mechanism involved.…”
Section: Lipid Metabolism Associated With Agingsupporting
confidence: 91%
See 1 more Smart Citation
“…In another study, senescent human peritoneal mesothelial cells were found to store and secrete substantially more phosphatidylcholines than young cells. 56 Our results are also in agreement with another large-scale targeted metabolic profiling study 5 in which there was a significant increase in specific phosphatidylcholines and sphingomyelins. It is suggested that the elevated serum levels of phospholipid in elderly are also involved in protection against oxidative stress; 5 however, further investigation is needed to understand the mechanism involved.…”
Section: Lipid Metabolism Associated With Agingsupporting
confidence: 91%
“…Naru et al 55 found that in vitro senescent human dermal fibroblasts cells had increased levels of a particular phosphatidylcholine species. In another study, senescent human peritoneal mesothelial cells were found to store and secrete substantially more phosphatidylcholines than young cells 56 . Our results are also in agreement with another largescale targeted metabolic profiling study 5 in which there was a significant increase in specific phosphatidylcholines and sphingomyelins.…”
Section: Lipid Metabolism Associated With Agingmentioning
confidence: 94%